The visual representation of Malaysian cultural identity in 1950s printmaking artworks / Noor A'yunni Muhamad ... [et al.] - Muhamad, Noor A'yunni; Tahir, Azian; Ramli, Ishak; S. Abu Bakar, Syed Alwi; Desa, Noor Enfendi; Mohd Aripin, Nur Adibah Nadiah; Arshad, Mohd Fawazie (Universiti Teknologi MARA, Perak, 2023)
Printmaking is one of the categories of visual arts that is still practiced and plays an important role in the development of visual arts in Malaysia. In the production of printmaking artworks, the representation of images or visuals is important in reflecting the artist's background, which is often closely related to understanding history, heritage, or culture. Nonetheless, there is a lack of written material that analyze the Malaysian cultural identity and its relevance to Malaysian printmaking art scene, particularly in the development of printmaking artworks. This research identifies the visual representation of Malaysian culture, which was portrayed in Malaysian printmaking artworks in the 1950s to justify the characteristic of Malaysian culture from the perspective of images and symbols. The method for identifying Malaysian culture is through an integrative literature review and a few 1950s printmaking artworks have been selected to be analyzed based on Malaysian cultural elements through a content analysis approach. The outcomes of this research concluded that elements of Malaysian culture in the form of visual representation consist of material cultures, namely norms, symbols, knowledge, ceremonies, festivals, language, social structure, social institutions, and non-material cultures, which consist of art, architecture, artifacts, clothing, pastimes, and foods. These elements of culture have been portrayed as a visual representation in selected 1950 printmaking artworks and it appears as evidence that reflects the Malaysian past environment. These cultural elements' identification through visual representations contributed to the existing literature by exploring more cultural elements that will expand the understanding of Malaysian culture from the perspective of the visual arts.